Pengembangan Instrumen Penilaian Teks Deskripsi Berbasis HOTS Berbantuan Aplikasi Quizizz di Kelas VII SMP Amalia Medan - Mariani, Titin; M. Hutagalung, Surya; Adisaputera, Abdurahman (Universitas Islam Sumatera Utara, 2025)
This study develops a Higher Order Thinking Skills (HOTS)-based assessment instrument for descriptive texts using Quizizz for seventh-grade students at SMP Amalia Medan. The research employs Sugiyono’s (2015) RD method, implementing seven stages: problem identification, data collection, product design, validation, revision, testing, and final revision. Validation by three experts yielded a 94% validity rate, confirming strong instrument reliability. Of 30 developed questions, 25 were valid (r 0.3291) with a reliability coefficient of 0.78 ( 0.60). The difficulty level was